Epidemiological Study and Surgical Outcome of Preauricular Sinus - Delwar, A H M; Mazumder, Jahangir Alam; Rashid, M Shazibur; Khan, Md Arif Murshed; Ahmed, Samsuddin; Rahaman, Md Mustafizur; Ahmed, Md Masuque; Rahman, Md Shafiqur (Journal of Comilla Medical College Teachers’ Association, 2023)
Background: Preauricular sinus (PrAS) is a common congenital external ear malformation affecting mainly children. Symptomatic Preauricular sinus and asymptomatic for unusual scar marks, surgery is the mainstay of treatment. Due to variationsin presentation and recurrence, surgeons practice different surgical procedures to treatthe Preauricular sinus. Objectives: To compare the relative frequency and incidence of the Preauricular sinus and find the best surgical approach. Methods: It is a cohort retrospective study of forty-four cases of Preauricular sinus in the Department of Otorhinolaryngology and Head-Neck Surgery, Comilla Medical College, Bangladesh, from 01-07-2016 to 31-06-2019. All forty-four patients were clinically diagnosed with Preauricular sinus and confirmed by history, examination, and investigations. Special investigations included Audiological analysis and Ultrasonography of the renal system. Results: Theincidence of Preauricular sinus out of 1,16,128 patients in the outpatient department was 44 (0.05%), and out of inpatient routine operative 2738 patients were 1.61%. Fortypatients (90.90%) were treated by traditional sinusectomy, and the rest of the four patients (9.10%) were treated by extended supra-auricular sinusectomy procedures. Relapse was taken place in two patients (4.54%). Gender issuance shows that female was 24(54.54%) and males was 20(45.46%). The age distribution exhibited in the case of children was 34(77.27%), and adult, was 10(22.73%). Anatomical site allocation reveal that right side was 22(50%), left side was 20(45.45%), bilateral was 2(4.55%) whereas unilateral was 42(95.45%). Presenting features display non-infected putty like discharge was 21(47.72%), infected abscess was 19(43.18%) and asymptomatic was 4(9.1%). A syndrome related tothe Preauricular sinus was not found in our study. Conclusion: Children were more affected by the Preauricular sinus as a congenital disease. Incidence and recurrence are always countable fromthe perspective of treatment. As surgery is the treatment principle, it should be perfect without recurrence. We appreciate the supra-auricular approach for the excision of the Preauricular sinus, which best complements the patient’s wishes. J Com Med Col Teachers Asso Jan 2023; 27(1): 09-13